Considerations on the monetary policy framework of the European Central Bank - Andrea Giorgio Tosato (Central Bank of Malta, 2022)
This working paper offers some considerations on the monetary policy framework of the European Central Bank. The trade-offs arising from adopting a point target configuration over a range target one are assessed in terms of their flexibility vs. inflation anchoring properties. This layout is then confronted with the policy framework in use in the euro area prior to the adoption of the new monetary strategy, which is interpreted as leaning on the side of flexibility. The increased likelihood of dis-anchoring of long-term inflation expectations experienced in the euro area since 2013, however, suggests that the policy framework could benefit from a rebalancing towards a formulation with stronger anchoring properties. The inflation aim of the ECB could thus be reformulated with the introduction of a symmetric 2%-point target. By evaluating this arrangement in terms of the price stability definition, two regions emerge where either the policy aim (symmetric 2%-point target) or the price stability definition (between 0% and 2%) are satisfied, but not both. To avoid any inconsistency in the policy framework, an inflation aim centred at 2% requires an amendment of the price stability definition.
Keywords: E42; E52; E58; 330; Inflation Targeting; European Central Bank; Inflation Expectations; Price Stability